Future Livestock Systems: Scenario-guided policy review workshop - Kiker, Gregory A.; Rutting, Lucas; Thornton, Philip K. (2019)
The recent CCAFS and the LSIL scenarios process focuses on contextual drivers of change for agriculture and food security – climate change and socio-economic changes (e.g. in markets, governance, broad economic developments, infrastructure).